2021
DOI: 10.1016/j.biopha.2020.111138
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminoquinoline compounds from the Spanish flu to COVID-19

Abstract: Graphical abstract Mechanisms of action of 4-aminoquinoline compounds on viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…HCQ generated sense of belief for the treatment and prevention of COVID-19 due to its in vitro virucidal action against SARS-CoV-2 28 . Hydroxychloroquine (HCQ), a less toxic derivative of chloroquine (CQ) is part of the 4-aminoquinoline family compounds 29 . HCQ was initially used as an anti-malarial agent and presently is best recognized as an immunomodulatory and anti-inflammatory agent for the treatment of autoimmune diseases likes rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HCQ generated sense of belief for the treatment and prevention of COVID-19 due to its in vitro virucidal action against SARS-CoV-2 28 . Hydroxychloroquine (HCQ), a less toxic derivative of chloroquine (CQ) is part of the 4-aminoquinoline family compounds 29 . HCQ was initially used as an anti-malarial agent and presently is best recognized as an immunomodulatory and anti-inflammatory agent for the treatment of autoimmune diseases likes rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…HCQ was initially used as an anti-malarial agent and presently is best recognized as an immunomodulatory and anti-inflammatory agent for the treatment of autoimmune diseases likes rheumatoid arthritis and systemic lupus erythematosus. The proposed primary mechanism for anti-viral action of HCQ is alkalinization of endosomes and lysosomes and subsequent rise in pH leading to inhibition of viral nucleic acid replication, protein glycosylation, viral assembly and transportation, and release of new viral particles 28 , 29 . Additionally, HCQ can also block viral uptake by inhibiting the glycosylation of the ACE-2 receptor at the plasma membrane to which viral spike protein binds for cellular entry 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study concluded that quinine has an antiviral effect against influenza viruses by consistently slowing the course of infection with the influenza virus. 38 Quinine’s antiviral activity has also been demonstrated in several other viruses, such as H1N1 39 , Influenza A virus (IAV), Human Immunodeficiency Virus (HIV), Zika virus, Ebola and dengue. 40 , 41 In addition, the antiviral effect of quinine was described by Baroni at al, who evaluated QS in HaCat HSV-1 infected cells.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, continuous clinical investigations were carried out using two approved drugs of 4‐aminoquinoline scaffold for example, chloroquine (CQ) and hydroxychloroquine (HCQ). [ 33 ] Due to less toxicity and high solubility of hydroxychloroquine as compared to chloroquine, it was widely used during the COVID‐19 pandemic as an antiviral agent for the treatment and further investigations. Reported studies showed in vitro activity of HCQ against SARS‐CoV‐2.…”
Section: Anti‐infective Potential Of 4‐substituted Quinolinesmentioning
confidence: 99%